EFFORTS AND ROLE OF THE TOURISM DEPARTMENT IN TOURISM IN DEMAK DISTRICT BASED ON DEMAK REGIONAL REGULATION NUMBER 5 OF 2019 - Sunardi, Sunardi; Dian Lestari, Devi (Jurnal Meta-Yuridis, 2024)
Tourism is all activities related to tourism and is multidimensional and multidisciplinary in nature which emerges as a manifestation of the needs of each person and country as well as interactions between tourists and local communities, fellow tourists, the Government, Regional Government and entrepreneurs. In this thesis, the researcher is concerned with the efforts and role of the Tourism Department in tourism in Demak Regency.Theaim of this main problem is to find out the efforts and role of the Tourism Department in Tourism in Demak RegencyThe Tourism Office in its efforts to develop tourism in Demak Regency has gone well but has not been optimal in several strategies. Strategies that have bee n successful include increasing religious tourism and have not yet integrated it with other tourism potential